Long-term ultrasound insights into camelid urology: a retrospective analysis of urinary tract disorders in 1,100 dromedary camels (Camelus dromedarius) (2012–2025) - Tharwat, Mohamed; Elmoghazy, Hazem M. M. (Frontiers in Veterinary Science, 2026)
IntroductionUrinary tract disorders are common in dromedary camels and present diagnostic challenges due to non-specific clinical signs and limited field diagnostic tools. Ultrasonography is a valuable, non-invasive modality for evaluating renal and lower urinary tract abnormalities. This long-term retrospective study aimed to describe the ultrasonographic findings associated with urinary tract disorders in dromedary camels and to assess the diagnostic utility of ultrasonography as a primary imaging modality.MethodsRecords of 1,100 camels (3 months−20 years) examined between 2012 and 2025 were reviewed. Based on primary clinical presentation and ultrasonographic observations, animals were classified into six descriptive groups: hemorrhagic (G1), inflammatory (G2), infectious (G3), obstructive (G4), traumatic (G5), and neoplastic (G6). Sonographic features were summarized descriptively, and ultrasound-guided aspiration was performed when indicated for pathogen identification.ResultsG1 (n = 300) included hemorrhagic conditions characterized by hematuria, bladder clots, thickened or corrugated bladder walls, nephrolithiasis, hydronephrosis, renal abscesses, pyelonephritis, and bladder rupture. G2 (n = 332) comprised inflammatory disorders, including cystitis with thickened bladder walls and echogenic luminal deposits, balanitis with pelvic urethral dilation, and bladder paralysis with severe distension and hyperechoic sediment. G3 (n = 179) involved infectious diseases, presenting with single or multiple renal abscesses; ultrasound-guided aspiration identified Staphylococcus lugdunensis and Staphylococcus aureus in sampled cases. G4 (n = 214) consisted of obstructive disorders associated with urinary retention, urethral dilation, bladder distension, and renal or bladder calculi producing acoustic shadowing. G5 (n = 73) included traumatic conditions such as uroperitoneum and bladder rupture, identified ultrasonographically by free abdominal fluid, floating viscera, and collapsed thick-walled bladders. G6 (n = 2) represented neoplastic disease with irregular renal masses of mixed echogenicity.ConclusionUltrasonography provided a detailed assessment of a wide range of urinary tract disorders in dromedary camels and proved to be a practical, non-invasive diagnostic tool in both field and hospital settings. The retrospective data demonstrate its value in identifying lesion location, tissue alterations, and associated structural abnormalities, even when laboratory or advanced imaging data are incomplete. These findings support ultrasonography as a primary diagnostic method for urinary tract evaluation, enhancing clinical recognition and management of urinary disorders in camels.